Evaluation of wet corn gluten feed as an ingredient in diets for lactating dairy cows - M. J. VanBaale; Michael V. Scheffel; Evan C. Titgemeyer; John E. Shirley (Kansas Agricultural Experiment Station Research Reports, 1999)
Thirty-two Holstein cows were used in two 2x2 Latin squares with 28-day periods to evaluate the effect of including wet corn gluten feed in diets for lactating dairy cows. Wet corn gluten feed (WCGF) was fed to cows housed in freestalls at 20% of the diet dry matter. Cows fed WCGF consumed more dry matter, and produced more milk and more energy-corrected milk than cows fed the control diet. Production efficiency was not different between diets. The percentages of fat and protein in milk were not different between diets, but yields of all milk components were improved by including WCGF in the diet. Body weight and condition score were not affected by treatment. Plasma glucose, total amino acids, and urea nitrogen were similar between cows fed the control and WCGF diets. WCGF is an excellent feed for lactating dairy cows when included in the diet at 20% of the dry matter. Further studies are warranted to determine the upper limits of its dietary inclusion.; Dairy Day, 1999, Kansas State University, Manhattan, KS, 1999;
Keywords: Dairy Day; 1999; Kansas Agricultural Experiment Station contribution; no. 00-136-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 842; Dairy; Wet corn gluten feed; Lactating cows; Milk Yield